Abacavir Hypersensitivity Reaction Reporting Rates During a Decade of HLA‐B*5701 Screening as a Risk‐Mitigation Measure. Issue 1 (11th December 2018) - Stainsby, Chris M.; Perger, Teodora M.; Vannappagari, Vani; Mounzer, Karam C.; Hsu, Ricky K.; Henegar, Cassidy E.; Oyee, James; Urbaityte, Rimgaile; Lane, Charlotte E.; Carter, Lindsay M.; Pakes, Gary E.; Shaefer, Mark S.
Abstract : Introduction: Human leukocyte antigen (HLA)‐B*5701 screening identifies patients at increased risk for abacavir (ABC) hypersensitivity reaction (HSR). Screening was adopted in GlaxoSmithKline and ViiV Healthcare clinical trials in 2007 and human immunodeficiency virus treatment guidelines in 2008. Company meta‐analyses of trials pre–HLA‐B*5701 screening reported HSR rates of 4–8%. We analyzed the effectiveness of HLA‐B*5701 screening on reducing HSR rates using clinical trial, Observational Pharmaco‐Epidemiology Research & Analysis (OPERA) cohort, and spontaneous reporting data. Methods: A meta‐analysis examined 12 trials in 3063 HLA‐B*5701–negative patients receiving an ABC‐containing regimen from April 9, 2007, to September 22, 2015. Potential cases were identified using prespecified Medical Dictionary for Regulatory Activities (MedDRA) preferred terms ( drug hypersensitivity, hypersensitivity, anaphylactic reaction, anaphylaxis ) and adjudicated against a Company ABC HSR case definition. Investigator‐diagnosed cases were identified and rates were calculated. In the OPERA cohort, 9619 patients initiating their first ABC‐containing regimen from January 1, 1999, to January 1, 2016, were identified. Patients were observed from regimen start until the earliest‐following censoring event: ABC discontinuation, loss to follow‐up, death, or study end (July 31, 2016). OPERA physicians evaluated events against OPERA definitions for definite/probable cases of ABC HSR; rates were calculated pre‐ and post‐2008. The Company case definition was used to identify spontaneously reported cases for four marketed ABC‐containing products; reporting rates were calculated using estimated exposure from sales data, through December 31, 2016. Results: Suspected ABC HSR rates were 1.3% or less in the meta‐analysis. In the OPERA cohort, the rate was 0.4% among patients initiating ABC post‐2008 versus 1.3% pre‐2008 (p<0.0001). Spontaneous reporting rates were low post‐2008 (54 to 22 cases per 100, 000 patient‐years exposure [PYE]) versus pre‐2008 (618 to 55 cases per 100, 000 PYE). Conclusions: Clinically suspected ABC HSR rates were 1.3% or less in HLA‐B*5701–negative patients. Recognizing their limitations, data from the OPERA cohort and spontaneous reporting indicate that HLA‐B*5701 screening has reduced reporting rates of suspected HSR in clinical practice. Where screening for HLA‐B*5701 is standard care, patients should be confirmed negative for this allele before starting ABC treatment.